Evolutionary patterns of chromosomal instability and mismatch repair deficiency in proximal and distal colorectal cancer. (5th November 2021) - Golas, Mariola Monika; Gunawan, Bastian; Cakir, Meliha; Cameron, Silke; Enders, Christina; Liersch, Torsten; Füzesi, Laszlo; Sander, Bjoern
Abstract: Aim: Colorectal carcinomas (CRCs) progress through heterogeneous pathways. The aim of this study was to analyse whether or not the cytogenetic evolution of CRC is linked to tumour site, level of chromosomal imbalance and metastasis. Method: A set of therapy‐naïve pT3 CRCs comprising 26 proximal and 49 distal pT3 CRCs was studied by combining immunohistochemistry of mismatch repair (MMR) proteins, microsatellite analyses and molecular karyotyping as well as clinical parameters. Results: A MMR deficient/microsatellite‐unstable (dMMR/MSI‐H) status was associated with location of the primary tumour proximal to the splenic flexure, and dMMR/MSI‐H tumours presented with significantly lower levels of chromosomal imbalances compared with MMR proficient/microsatellite‐stable (pMMR/MSS) tumours. Oncogenetic tree modelling suggested two evolutionary clusters characterized by dMMR/MSI‐H and chromosomal instability (CIN), respectively, for both proximal and distal CRCs. In CIN cases, +13q, −18q and +20q were predicted as preferentially early events, and −1p, −4 ‐and −5q as late events. Separate oncogenetic tree models of proximal and distal cases indicated similar early events independent of tumour site. However, in cases with high CIN defined by more than 10 copy number aberrations, loss of 17p occurred earlier in cytogenetic evolution than in cases showing low to moderate CIN. Differences in the oncogenetic trees were observed for CRCs with lymph node and distant metastasis. Loss of 8p was modelled as an early event in node‐positive CRC, while +7p and +8q comprised early events in CRC with distant metastasis. Conclusion: CRCs characterized by CIN follow multiple, interconnected genetic pathways in line with the basic 'Vogelgram' concept proposed for the progression of CRC that places the accumulation of genetic changes at centre of tumour evolution. However, the timing of specific genetic events may favour metastatic potential.